The Role of Interior Designers to Humanistic Design throughout a Framework of Social and Community Activities: Humanistic Design - Jonatan, Lisa; Maximillian, Arnold; Chandrahera, Yuma (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2023)
An interior designer, has apparent role to provide a humanist design as a solution to emerging social problems. This action is reflected in the community service activities that performed with the Buddhist Tzu Chi Foundation Bandung on humanitarian projects. This project is part of the Merdeka Belajar - Kampus Merdeka program that conducted by Maranatha Christian University. The initial problem that arises in this humanitarian project is the absence of assistance in the context of design, so the output results often become not ideal when viewed from the user’s humanist. In order to obtain ideal results, it is necessary to apply design rules and principles into the design of interior spaces. The method in this activity is assistance through science and technology diffusion, in the form of support in creating spatial designs that aim to provide convenience for activities and decent residential spaces. The results of this activity are the layout and zoning of space in degenerative treatment social service activities and the design of healthy homes in one of the densely populated neighborhoods in the city of Bandung.